2022
DOI: 10.1186/s13595-022-01125-z
|View full text |Cite
|
Sign up to set email alerts
|

Altitude is a better predictor of the habitat requirements of epixylic bryophytes and lichens than the presence of coarse woody debris in mountain forests: a study in Poland

Abstract: Key message In order to preserve the continuity of epiphytic and epixylic cryptogamic flora, two things are essential: maintaining the near-natural character of a forest community in relation to the montane zonation and more sustainable forest management in relation to deadwood. Context Lichens and bryophytes are common species that inhabit dead wood. The relationship between their habitat requirements, which can be expressed by their Ellenberg ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
(68 reference statements)
2
1
0
Order By: Relevance
“…Our results showed that elevation is an important factor that limits snag distribution in the secondary forest ecosystems of the Kanghe Mountains, which agrees well with many other studies [18,[40][41][42][43]. The average DBH and basal area decreased as elevation decreased, which may be due to competition for limited resources.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results showed that elevation is an important factor that limits snag distribution in the secondary forest ecosystems of the Kanghe Mountains, which agrees well with many other studies [18,[40][41][42][43]. The average DBH and basal area decreased as elevation decreased, which may be due to competition for limited resources.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, snags with larger diameters provide nests, perches, roost sites, foraging substrates, song posts, and escape cover for organisms such as amphibians, arthropods, birds, and small mammals [13][14][15][16]. When they fall, snags also offer germination and growth substrates for lichens, various types of fungi, and bryophytes [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The same pattern was detected for solar radiation: cluster 1 displayed solar radiation values higher than 1000 KW/m 2 , while the values of cluster 2 were substantially below this threshold (see Table S1). The association between elevation and solar radiation has been reported elsewhere, suggesting that elevation may be a good proxy for light availability in mountain environments [35]. Our results suggested that elevation and solar radiation were the environmental variables most associated with the differences detected between the lichen communities characterizing the two clusters of sites.…”
Section: Discussionsupporting
confidence: 82%
“…Relevant ecological variables explaining the occurrence of the species are rainfall, canopy closure, amount of necromass in a late state of decay, watercourses and altitude (Chmura & al. 2002).…”
Section: B -Ecologymentioning
confidence: 99%